2017
DOI: 10.1111/1751-7915.12596
|View full text |Cite
|
Sign up to set email alerts
|

Differences in internalization and growth of Escherichia coli O157:H7 within the apoplast of edible plants, spinach and lettuce, compared with the model species Nicotiana benthamiana

Abstract: SummaryInternalization of food‐borne bacteria into edible parts of fresh produce plants represents a serious health risk. Therefore, internalization of verocytotoxigenic E. coli O157:H7 isolate Sakai was assessed in two species associated with outbreaks, spinach (Spinacia oleracea) and lettuce (Lactuca sativa) and compared to the model species Nicotiana benthamiana. Internalization occurred in the leaves and roots of spinach and lettuce throughout a 10 day time‐course. The plant species, tissue type and inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 74 publications
1
59
0
Order By: Relevance
“…Seeds were stratified for 48h at 4°C and germinated under a 16/8 h light/dark cycle at 20°C in MLR-350 growth chamber (Panasonic). Nicotiana benthamiana plants expressing mOrange-LTI6b fluorescent protein as a plasma membrane marker (mOrg-LTI; [32]) were used for confocal imaging. Transgenic and wild-type Nicotiana benthamiana plants were grown in commercial compost and maintained under glasshouse conditions of 16/8 h light/ dark cycle, daytime temperature 26°C maximum, nighttime 22°C for 4-5 weeks before use.…”
Section: Plant Lines and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds were stratified for 48h at 4°C and germinated under a 16/8 h light/dark cycle at 20°C in MLR-350 growth chamber (Panasonic). Nicotiana benthamiana plants expressing mOrange-LTI6b fluorescent protein as a plasma membrane marker (mOrg-LTI; [32]) were used for confocal imaging. Transgenic and wild-type Nicotiana benthamiana plants were grown in commercial compost and maintained under glasshouse conditions of 16/8 h light/ dark cycle, daytime temperature 26°C maximum, nighttime 22°C for 4-5 weeks before use.…”
Section: Plant Lines and Growth Conditionsmentioning
confidence: 99%
“…Leaves of 4-5 week old wild type and mOrg-LTI [32] expressing Nicotiana benthamiana plants were syringe infiltrated with Agrobacterium tumefaciens GV3101 pMP90 containing expression plasmids for each receptor-like kinase alongside p19, each at an OD600 of 0.1. Plants were maintained under standard growth conditions for 48-60h before use in experiments.…”
Section: Transient Expression In N Benthamianamentioning
confidence: 99%
“…More recently various plant foods such as spinach, tomato, lettuce and fresh fruits have been identified as sources (Grant et al 2008;Herman et al 2015;Denis et al 2016). Initially these foods were thought to be fecally contaminated, but recent reports suggest growth of E. coli O157:H7 (Brandl 2008;Wright et al 2013;Wright et al 2017) in tissues of salad leaves and tomatoes. Upon inoculation from an unknown source, the enteric bacteria multiply inside the growing plant, and cannot be removed through surface treatment such as washing.…”
Section: Introductionmentioning
confidence: 99%
“…Colonisation of the E. coli O157:H7 isolate (ZAP1589) was quantified on spinach and lettuce, and for both isolates (ZAP1589 and Sakai) on sprouted seeds. Our previous in planta data for lettuce and spinach plants showed that the highest levels of E. coli isolate Sakai occurred on spinach roots (73). Inoculation of spinach and lettuce with the high dose (10 7 cfu ml −1 ) of E. coli isolate ZAP1589 also resulted in higher levels of bacteria on the roots compared to leaves, with similar levels on spinach and lettuce roots, e.g.…”
Section: Resultsmentioning
confidence: 94%
“…The apoplast contains metabolites, such as solutes, sugars, proteins and cell wall components (54) and as such provides a rich environment for many bacterial species, both commensal bacteria and human pathogens (20, 28). The rate of STEC internalisation is dependent on multiple factors including the plant species and tissue (73) and how plants are propagated (17-19). Specificity in the response of STEC to different plant species and tissue types has been demonstrated at the transcriptional level (9, 38).…”
Section: Introductionmentioning
confidence: 99%